Characteristics Of Stunting Children With Background History Of Family Demography And Maternal Reproductive In Pasaman And Pasaman Barat District, West Sumatera - Masrul Masrul (Journal of Midwifery, 2018)
About a quarter of children under five years old worldwide are affected by stunting. There are 7.6 million (37%) Indonesian children suffering from stunting and the rate of stunting in West Sumatra is above the national rate which is 46.1%. That number shows that many of children need more attention, because they don't grow well. The purpose of this study was to determine thecharacteristics of stunting children based on the background history of family demographic and maternal reproductive. Data was obtained by interviewing respondents and data were analyzed using statistical tests. Respondents consisted of stunting children and normal children in Pasaman District and West Pasaman District. It is known that the incidence of stunting associated with respondent demographics and history of birth which is the length of born infant, education of head of the family, form of the core family, social and economic.